Modular origami-inspired kinematic metamaterials - Yang, Y (2020)
This dissertation proposed a kinematic-based construction method for reconfigurable mechanical metamaterials. This was achieved by entrenching kinematic mechanisms with predefined motion paths within the unit cells of the metamaterial and connecting the units according to carefully chosen topology pattern. The developed metamaterials are able to perform complex transformation between different configurations, which brings superior tuneable physical properties. The major findings of this dissertation are in following four areas.